Analysis of The Readiness of The Regional Government of Malinau District North Kalimantan Province in Commemorate Digital Transformation - Tria Hilda; Ika Sartika; Hadi Prabowo; Petrus Polyando (Institut Pemerintahan Dalam Negeri, 2024)
One of the efforts to realize the goals of bureaucratic reform is the modernization of the government bureaucracy which focuses on the orientation of public services to community satisfaction through optimizing the use of information technology. The purpose of this research is to analyse the readiness of the Regional Government of Malinau Regency in commemorate digital transformation and to identify supporting and inhibiting factors for the readiness of the Regional Government of Malinau Regency in commemorate digital transformation. This study uses a qualitative research design with descriptive methods, by adapting the An Integration Information Rich E-Readiness Assessment Tool readiness analysis model, proposed by Mutula & Brakel 2006. This research uses a triagulation analysis method on observation data, interviews and documentation in the field. The research results of the five dimensions of assessment show 1) Information Readiness with information access indicators categorized as ready and information mechanism indicators categorized as quite ready; 2) Institutional Readiness with Organizational Structure indicators categorized as ready, ICT Policy indicators categorized as quite ready and ICT Budget Readiness categorized as ready; 3) HR readiness with HR composition indicators categorized as quite ready, ICT HR qualification indicators categorized as unprepared, and ICT HR preparation indicators categorized as unprepared. 4) Infrastructure Availability with hardware and software infrastructure indicators categorized as ready and internet connection indicators categorized as quite ready; 5) External Environment Readiness with telecommunications service quality indicators categorized as quite ready.